How can the Data Revolution contribute to climate action in smallholder agriculture? - Etten, Jacob van; Steinke, Jonathan; Wijk, Mark T. van (2017)
In this article, we discuss the ongoing Data Revolution in relation to climate action in agriculture. Data are highly relevant for climate action, as climate change makes current local knowledge increasingly irrelevant and requires smarter management of agricultural systems. We discuss five datarelated concepts and explore how they are linked with agricultural climate action: lean data, crowdsourcing, big data, ubiquitous computing, and information design. We show practical examples for each of these concepts. There are many opportunities for improving agricultural development projects, providing new services to smallholder farmers, and generating better information for policy- and decision-making. Making the Data Revolution work for smallholder farmers’ climate action not only takes further technological development, but also requires careful governance and public investment to avoid a few actors taking over the current innovation space and stifle further development.